Pemberdayaan Kelompok Tani Hutan Melalui Peningkatan Kapasitas Ketrampilan pada Penyeduhan Kopi Robusta - Maksum, Ali; Purbowati, Ike Sitoresmi Mulyo; Jaya, Gigieh Henggar; Novitasari, Dian (Jurnal Ilmiah Pangabdhi, 2025)
The growth of coffee consumption in Indonesia in 2025 is projected to reach an average of 7% per year with total coffee consumption reaching 450,000 tons/year. The shift in coffee consumption patterns of generation Z from tubruk coffee to various coffee brewing variants such as cold brew, filter coffee, and iced coffee is an obstacle for KTH Tani Jaya in marketing coffee products at the Kepuh Tourism Location. Based on direct observations in the field, there are problems, namely: The Forest Farmers Group "Tani Jaya" has not mastered the techniques and variations of coffee brewing. The solution offered is coffee brewing technology to overcome the problem of the coffee brew served being predominantly bitter. The Community Service method that will be used is socialization, training, and mentoring in the application of coffee brewing technology. To measure the impact of the technology transfer provided, a descriptive analysis is used based on measuring the level of knowledge, understanding and skills regarding coffee brewing. The results of the training and mentoring that have been implemented have resulted in an increase in the level of knowledge, understanding and skills of coffee brewing by 39.4%, 48.5% and 50%, respectively.